Promoting The Learning Quality of Islamic Elementery School Through Constructive - Inovative Model - Hilma Pami Putri (Jurnal Educative: Journal of Educational Studies, 2019)
Learning is interpreted as a process of obtaining behavioral changes as a result of getting knowledge and experience in doing interaction with the environment. The problem found in Islamic Elementery School 1 Pasaman (MIN 1 Pasaman) was the way the teacher tought the students and the teacher never create the innovative environment to make the students to be able to construct their ideas in learning. The teachers were still not familiar with the name and the application of constructive innovative learning models in order to create the fun learning for the students. The situation impacts to the student’s development and achievement during teaching and learning process. It leads the team to do the community service research to the application of constructive - innovative models to improve the quality of teaching and learning in MIN 1 Pasaman. The result of this community service shown that the teachers already able to comprehend the constructive -inovative learning model in teaching and learning process, and the teacher can apply various types of learning model as well as able to design a good lesson plan about constructive and innovative model in the classroom.Belajar diartikan sebagai proses perubahan perilaku sebagai hasil dari mendapatkan pengetahuan dan pengalaman dalam melakukan interaksi dengan lingkungan. Masalah yang ditemukan di Madrasah Ibtidaiyah 1 Pasaman (MIN 1 Pasaman) adalah cara guru mengajar siswa dan guru tidak pernah menciptakan lingkungan belajar yang inovatif untuk membuat siswa dapat membangun ide-ide mereka dalam belajar. Para guru masih belum tahu dengan nama dan juga cara menerapkan dengan model pembelajaran konstruktif- inovatif agar pembelajaran menyenangkan bagi siswa. Situasi ini berdampak pada perkembangan dan prestasi siswa selama proses belajar mengajar. Keadaan ini mengarahkan tim untuk melakukan penelitian pengabdian masyarakat pada penerapan model inovatif - konstruktif untuk meningkatkan kualitas pengajaran dan pembelajaran di MIN 1 Pasaman. Hasil pengabdian masyarakat ini menunjukkan bahwa para guru sudah mampu memahami model pembelajaran konstruktif-inovatif dalam proses belajar mengajar, dan guru dapat menerapkan berbagai jenis model pembelajaran yang konstruktif serta mampu merancang rencana pembelajaran yang konstruktif dan inovatif di kelas.Kata Kunci: pembelajaran, konstruktif- innovative, model